The Management of General Election Commission in the Implementation of the 2024 Simultaneous Elections in Banyumas Regency - Rapika Trisma Nurjanah; Indah Ayu Permana Pribadi; Chamid Sutikno; Ariesta Amanda; Zaula Rizqi Atika (Political Sciences Program Study, 2025)
This study was motivated by the suboptimal management of the Banyumas Regency General Election Commission (KPU) in the implementation of the 2019 Simultaneous Elections. This study aims to determine how the General Election Commission (KPU) will manage the implementation of the 2024 Simultaneous Elections in Banyumas Regency. This research uses a qualitative method with a case study approach. The data used consists of primary and secondary data obtained through observation, interviews, and documentationThe results of the study show that the Banyumas Regency KPU has implemented effective management in organizing the 2024 Simultaneous Elections. However, several challenges were still encountered during implementation, such as the composition of human resources that was not yet ideal, changes in terms of office in the middle of the stages, not having its own logistics warehouse, weather and geographical constraints, and errors in the SIREKAP system. This study is expected to serve as evaluation material for the Banyumas Regency KPU. In addition, it is hoped that it will contribute to knowledge about management theory from a public administration perspective, thereby enriching understanding of management in public institutions and providing recommendations for improving the quality of election administration in the future.